The Combined Effect of Safety Specific Transformational Leadership and Safety Consciousness on Psychological Well-Being of Healthcare Workers - Irshad, Muhammad; Majeed, Mehwish; Khattak, Sana Aroos (Frontiers in Psychology, 2021)
Occupational health researchers have begun to realize that the psychological well-being of healthcare workers who are providing treatment against COVID-19 is deteriorating. However, there is minimal research conducted on it, particularly in the context of leadership. The current study aims to fill this important gap by identifying critical factors that can enhance the psychological well-being of healthcare workers. We proposed that safety specific transformational leadership enhances psychological well-being among healthcare workers, and COVID-19 perceived risk mediates this relationship. Furthermore, the safety conscientiousness of healthcare workers was proposed to be a boundary condition that enhances the negative relationship between safety-specific transformational leadership and COVID-19 perceived risk. Data were collected from healthcare workers (N=232) treating COVID-19 patients in the hospitals of Pakistan through well-established adopted questionnaires. The discriminant and convergent validity of the data was tested through confirmatory factor analysis by using AMOS statistical package. The mediation and moderation hypotheses were tested by using PROCESS Macro by Hayes. The results showed that safety specific transformational leadership enhances psychological well-being among healthcare workers, and COVID-19 perceived risk mediates this relationship. Moderation results also confirmed that safety conscientiousness moderates the relationship between safety specific transformational leadership and COVID-19 perceived risk. This study offers implications for both researchers and practitioners.